Effects of Joint Spacing on Static Bearing Capacity of Rock Foundations in the case of Punching Failure - Sharifzadeh, Mostafa; Imani, S.; Fahimifar, A.
In this paper, using distinct element method, static bearing capacity of rock foundations containing one, two or three joint sets is investigated in the case of punching failure. The effect of joint spacing is incorporated in the analyses using a dimensionless factor, named spacing ratio (SR). Different values for SR are selected and variation of bearing capacity versus SR is monitored. Then, the magnitude of SR in which the bearing capacity is not changed significantly, is determined. The findings show that for SR<30, increasing SR results in decreasing bearing capacity, while for SR>30, joint spacing does not affect bearing capacity, significantly. Hence, SR=30 can be used as a criterion for analysis of rock foundations either as an equivalent continuum or a discontinuous medium. Using this criterion, it will tend to greatly reduce the time required for bearing capacity analysis of rock foundations.